2015
DOI: 10.1016/j.ajpath.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Smoking-Induced Expression of the GPR15 Gene Indicates Its Potential Role in Chronic Inflammatory Pathologies

Abstract: Despite the described clear epigenetic effects of smoking, the effect of smoking on genome-wide gene expression in the blood is obscure. We therefore studied the smoking-induced changes in the gene-expression profile of the peripheral blood. RNA was extracted from the whole blood of 48 individuals with a detailed smoking history (24 never-smokers, 16 smokers, and 8 ex-smokers). Gene-expression profiles were evaluated with RNA sequencing, and results were analyzed separately in 24 men and 24 women. In the male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 47 publications
4
43
0
Order By: Relevance
“…In particular, loci cg07826859 (MYO1G) and cg19859270 (GPR15) have been reported to play a role in the formation of chronic inflammation via regulating the activity of T cells. 32,33 Locus cg25189904 is located on the south shore of a CpG island spanning the promoter of GNG12 that has been suggested to be an important factor in the overall inflammatory signaling cascade. 34 Moreover, another 3 loci are mapped to genes linked to the risks of various age-related cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, loci cg07826859 (MYO1G) and cg19859270 (GPR15) have been reported to play a role in the formation of chronic inflammation via regulating the activity of T cells. 32,33 Locus cg25189904 is located on the south shore of a CpG island spanning the promoter of GNG12 that has been suggested to be an important factor in the overall inflammatory signaling cascade. 34 Moreover, another 3 loci are mapped to genes linked to the risks of various age-related cancers.…”
Section: Discussionmentioning
confidence: 99%
“…41 However, several following studies have found the highly significant (with genome-wide significance) hypomethylation and increased expression of GPR15 in smokers. [42][43][44] Another study analyzed the RNA expression from the whole blood together with methylation profile and found highly significant upregulation of GPR15 expression in the blood that correlated with the hypomethylation of the GPR15 locus. 45 These authors found that the methylation was reversible after smoking cessation.…”
Section: Gpr15 and Smokingmentioning
confidence: 99%
“…46 While GPR15 hypomethylation correlates very well with the increased RNA expression, with AHRR only methylation changes have been described and no difference in gene expression has been found. 42 Therefore, GPR15 is almost the only gene related to smoking and having a clear correlation of methylation and expression.…”
Section: Gpr15 and Smokingmentioning
confidence: 99%
“… smoke-mediated redistribution of the interleukin (IL)-33 receptor, ST2, a member of the IL-1 pro-inflammatory cytokine family, resulting in increased expression on alveolar macrophages and natural killer cells, thereby potentiating the inflammatory potential of these cells [62]  increased expression of the G-protein-coupled receptor 15 gene (GPR15) in the blood of smokers resulting from hypomethylation of DNA [63]. This is an orphan receptor involved in the homing of effector, pro-inflammatory Th1 and Th17 cells to the colon [64].…”
Section: Pro-inflammatory Effects Of Smokingmentioning
confidence: 99%